THE IMPACT OF THE 2008-2009 GLOBAL CRISIS ON CORRUPTION: EVIDENCE FROM MANUFACTURERS IN CENTRAL ASIA AND EASTERN EUROPE - HALIL D. KAYA; ENGKU NGAH S. ENGKUCHIK (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2021)
In this study, we examine how the 2008-2009 Global Crisis has affected the informal payments/gifts paid by manufacturing firms. We compare the crisis period to the post-crisis period and found that the manufacturing firms believed that the incidence of bribes went down significantly after the crisis ended. When we differentiate the firms with respect to size, structure, legal form, gender of the owners, gender of the top manager, and whether or not they held an international quality certification, we find that the results hold for almost all classifications of firms. When we go into more detail and examine the incidence of bribes in customs/imports, courts, and taxes/tax collection, we found similar results. In almost all categories of firms, the respondents saw a significant drop in the incidence of bribes in all of these areas (i.e. customs/imports, courts, and taxes/tax collection) after the crisis ended.